(untitled) (Damascus University Journal of agriculture sciences, 2022)
The study was conducted in two citrus orchards at Al-Sanobar and Daba orchard in Lattakia governorate, (Syrian coast), during 2016-2017. This study aimed to determine predatory insects associated with Citricola scale Coccus pseudomagnoliarum (Kuwana) (Hemiptera: Coccidae). The predators belong to order Coleoptera which were considered with special importance because they were the most abundant (58.86%) of the total collected specimens: 506 individuals belonging to Coccinelidae family (54.35%), and 42 individuals of Cybocephalus fodori (Endrody-Younga), and Cybocephalidae family (4.51%). Two species of order Hemiptera were recorded, Geocoris ochropterus (Fieber) which belongs to family Geocoridae (11.60%), and Cardiastethus nazarenus (Reuter) which belongs to family Anthocoridae (16.76%). The abundance of Neuropteran predatory insects was 8.81%, two species belonged to Coniopterygidae: Conwentzia pineticola (Enderlein), Coniopteryx borealis (Tjeder), and Chrysoperla carnea (Stephens) that belongs to family Chrysopidae. One species of thrips, Karnyothrips flavipes (Jones), (Thysanoptera: Phlaeothripidae) was recorded with abundance of 3.65%. Eublemma scitula (Rambur) (Lepidoptera: Noctuidae) was recorded only at Daba orchard with abundance of 0.32%. The high biodiversity of predatory insects in the two studied areas suggested the importance of predatory insects as biological control agents against the Citricola scale insect C. pseudomagnoliarum.